Using multimedia material: effects on the knowledge of dental and speech-language pathology undergraduate students - Darliana Soares Gomes de Lima; Rita Tonocchi; Bianca Lopes Cavalcante Leão; Diana Conceição da Rocha Cardoso; Camila de Castro Corrêa; Maria Inês Pegoraro-Krook; Jeniffer de Cássia Rillo Dutka (Faculdade São Leopoldo Mandic, 2024)
ABSTRACT Objective: To compare the knowledge of Dental and Speech-Language Pathology undergraduate students about prosthesis treatment of velopharyngeal dysfunction in cases of cleft lip and palate before and after using educational multimedia material. Methods: The sample comprised 58 students (38 from the Dental program, and 20 from the Speech-Language Pathology program). A questionnaire on prosthesis treatment of velopharyngeal dysfunction in cases of cleft lip and palate was administered to a group of Dental and Speech-Language Pathology undergraduate students before and after they had access to educational multimedia (video) material on the topic approached in this study. Inferential statistics were used to investigate the significance of differences in correct answers before and after the Dental and Speech-Language Pathology undergraduate students had access to the multimedia/video material. Results: Before having access to the multimedia/video material, Speech-Language Pathology students had more correct answers (Dental: 4.89±1.31; SLP: 6.30±0.57). After having access to the material, the difference in correct answers between the students of both programs decreased (Dental: 6.00±0.66; SLP: 6.45±0.51), as Dental students' knowledge of the research topic increased. The comparison of the total sample before and after applying the multimedia/video material also demonstrated an increase in correct answers. Conclusion: Speech-Language Pathology students proved to have greater previous knowledge of palatal prostheses used for velopharyngeal dysfunction in cases of cleft lip and palate. Moreover, using the multimedia material possibly increased both Dental and Speech-Language Pathology students' knowledge of this topic.